Pesantren dan Fiqih Disabilitas : Studi Atas Pemahaman Santri Pondok Pesantren di Probolinggo Jawa Timur - Syamsuri Syamsuri (Universitas Nurul Jadid, 2019)
Abstract: The rise of disability fiqh studies in several universities is inversely proportional to the study of fiqh in pesantren. The pesantren, known as the place of tafaqquh fi al-din, did not hear its role in guarding the study of disability fiqh. This study tries to find out the understanding of santri in Probolinggo, East Java, about the disability fiqh and the factors that influence the understanding. The results of the study concluded that the understanding of santri in Probolinggo East Java on disability jurisprudence positions persons with disabilities as centers of study, has formal legal character, denies the ethical-moral approach, and is trapped in the discourse of rukhsah or the provision of dispensation. This understanding is influenced by reading material that is used as a reference, understanding that is transformed by teachers and senior santri, lack of experience in dealing with persons with disabilities in daily life and experience in following studies of disability with multiple perspectives.Keywords: Islamic School and Disability Fiqh